2021
DOI: 10.1002/pc.26136
|View full text |Cite
|
Sign up to set email alerts
|

Using infrared spectroscopy in combination with multivariate data analysis to predict residual strength of carbon fiber reinforced polymers after one‐sided thermal loading

Abstract: In this study, structural, mechanical, and chemical changes of one-sided thermally loaded carbon fiber reinforced polymers (CFRPs) are investigated. The aim is to test and reliably predict residual strength and delamination depth by using infrared spectroscopy. CFRP of different thicknesses (HexPly ® 8552/ IM7) were irradiated at varying heat fluxes over various time intervals. The inhomogeneously distributed matrix degradation was analyzed by means of attenuated total reflection Fourier transform infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They concluded that laminates with graphene structures had better mechanical properties than laminates without them. Vetter et al [ 10 ] studied the structural, mechanical, and chemical changes of one‐sided thermally loaded carbon fiber reinforced polymers. These additional reinforcement structures seem to have influence on the residual curing mechanics of these polymeric matrices.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that laminates with graphene structures had better mechanical properties than laminates without them. Vetter et al [ 10 ] studied the structural, mechanical, and chemical changes of one‐sided thermally loaded carbon fiber reinforced polymers. These additional reinforcement structures seem to have influence on the residual curing mechanics of these polymeric matrices.…”
Section: Introductionmentioning
confidence: 99%